Evaluation of a novel chlorine dioxide-based packaging technology to reduce human enteric virus contamination on refrigerated tomatoes and blueberries - Goulter, Rebecca M.; Frye, Jason W.; Kerr, William L.; Richard, Angela; Johnston, Michael; Jaykus, Lee-Ann (Frontiers in Sustainable Food Systems, 2023)
Chlorine dioxide (ClO2) is a promising antimicrobial with various food applications, one of those being inclusion in packaging. The purpose of this study was to evaluate a novel ClO2-based antimicrobial packaging system (InvisiShield™) for its efficacy against human norovirus (hNoV) and hepatitis A virus (HAV) in refrigerated fresh produce. Grape tomatoes or blueberries were placed in polypropylene trays and selectively inoculated with 6.0 log10 hNoV Genome Equivalent Copies (GEC; 20% stool suspension) or 6.2 log10 HAV GEC (cell culture lysate). Trays were heat sealed with a three-phase polymer film consisting of a base, channeling agent, and the ClO2 active (treatment); or control (no active) film and stored at 7°C for 24, 48 hrs, and 7 days. At each timepoint, the product was collected and processed for virus concentration using the sequential steps of elution and polyethylene glycol precipitation. Viruses in extracts were quantified using RNase-RT-qPCR. Log10 reductions (LR) in hNoV GEC for tomatoes were 2.2±1.3, 2.9±0.7, and 3.6±0.3, after 24, 48 hrs and 7 days, respectively. For blueberries, hNoV LR were 1.4±0.7, 1.7±0.5, and 2.7±0.2 GEC, respectively. Hepatitis A virus GEC LR were 0.4±0.2, 1.0±0.1, and 2.1±0.7 for tomatoes, and 0.1±0.2, 1.2±0.4, and 3.2±0.2 for blueberries, after 24, 48 hrs and 7 days, respectively. Position of the fruit in the tray did not affect inactivation (p>0.05). Sensory analysis on the treated tomato products revealed no statistically significant difference in appearance, flavor and texture attributes compared to the control. This novel ClO2-based antimicrobial packaging system effectively reduced concentrations of hNoV and HAV, as evaluated using reduction in GEC as proxy for infectivity, on grape tomatoes and blueberries after one day, with efficacy improving over 7 days of refrigerated storage. This technology shows promise as an antiviral treatment as applied to refrigerated fresh produce items.